2008
DOI: 10.1139/f07-191
|View full text |Cite
|
Sign up to set email alerts
|

Trait patterns of aquatic insects across gradients of flow-related factors: a multivariate analysis of Canadian national data

Abstract: Large-scale comparisons of aquatic bioassessment metrics based on taxonomic composition are currently constrained by the biogeographic limitations of taxon occurrence. The use of species trait patterns offers a possibility to overcome this constraint. We examine the assertion that the trait composition of aquatic insect communities changes in a consistent manner along similar environmental disturbance gradients by evaluating relationships between traits and three flow-related variables (velocity, water tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 22 publications
3
49
0
1
Order By: Relevance
“…The potential for traits to be correlated may confound causal inference in biomonitoring applications, and it suggests that a limited number of possible trait combinations or ''syndromes'' may exist Horrigan and Baird 2008). Thus, the relative sensitivity of individual and correlated traits to different stressors needs to be evaluated more fully.…”
Section: Trait Correlations and Combinationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential for traits to be correlated may confound causal inference in biomonitoring applications, and it suggests that a limited number of possible trait combinations or ''syndromes'' may exist Horrigan and Baird 2008). Thus, the relative sensitivity of individual and correlated traits to different stressors needs to be evaluated more fully.…”
Section: Trait Correlations and Combinationsmentioning
confidence: 99%
“…Thus, Statzner and Bêche (2010) argue that individual traits must not be used as indicators of many different stressors if reliable interpretations of trait responses are to be determined in multiple stressor environments. Using the trait modalities described by Poff et al (2006), Horrigan and Baird (2008) demonstrated that in a multistressor environment, selected trait modalities were influenced exclusively by changes in flow conditions and were not responsive to thermal and oxygen stress. Other traits were simultaneously responsive to the multiple stressors, and consequently had reduced diagnostic power.…”
Section: Trait-environment Linkagementioning
confidence: 99%
See 1 more Smart Citation
“…1), MTB approaches should focus on evolutionarily labile traits that have low statistical correlations (i.e., are phylogenetically independent) and are linked in a mechanistic way to a specific human impact to avoid confounding effects of trait syndromes (see also Horrigan and Baird 2008). This argument calls for constructing molecular (e.g., Ball et al 2005) or at least morphometric phylogenies of freshwater invertebrates and other groups to isolate the part of history that explains the presence of a given taxon in a given environment.…”
Section: Future Directions Of the Topicmentioning
confidence: 99%
“…For a mechanical, multispecies biomonitoring of human impact; across-taxa traits provide a robust tool independent of topographical, geographical, geological and seasonal change in species composition (Charvet et al 2000;Bêche et al 2006;McGill et al 2006;Horrigan & Baird 2008). Chironomid taxa data in this study have been translated into definable, long-term functional traits such as feeding groups or significant adaptations to river flow or chemical composition.…”
Section: Introductionmentioning
confidence: 99%